All the power in two hands: The role of CEOs in family IPOs. Issue 5 (October 2015) - Cirillo, Alessandro; Romano, Mauro; Pennacchio, Luca
Abstract The aim of this paper is to analyse how and if powerful CEOs affected IPO valuation in family firms that went public recently. To this end, we draw upon stewardship theory and make inferences based on a sample of family firms' IPOs that occurred on the Milan Stock Exchange between 2000 and 2011. By employing Finkelstein's (1992) framework, we rely on four sources of power (structural, ownership, expert and prestige) to build a multidimensional indicator of CEO power. Considering that such power is not directly observable, we use structural equation modelling as estimation methodology. Our findings reveal that outside investors positively evaluate the presence of a powerful CEO in the transition from private to public ownership. As such, if a family member serves as CEO the relationship is strengthened, while with a co-leadership structure IPO evaluations are less affected. Finally, the presence of a CEO who is also part of the family maximizes investor evaluations.